2017
DOI: 10.1038/ncomms14078
|View full text |Cite
|
Sign up to set email alerts
|

Global and local selection acting on the pathogen Stenotrophomonas maltophilia in the human lung

Abstract: Bacterial populations diversify during infection into distinct subpopulations that coexist within the human body. Yet, it is unknown to what extent subpopulations adapt to location-specific selective pressures as they migrate and evolve across space. Here we identify bacterial genes under local and global selection by testing for spatial co-occurrence of adaptive mutations. We sequence 552 genomes of the pathogen Stenotrophomonas maltophilia across 23 sites of the lungs from a patient with cystic fibrosis. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 44 publications
4
68
0
Order By: Relevance
“…Our maps reveal that local environments within the lung vary in terms of pathogen abundance, characteristics of biofilm at the molecular level, pharmaceutical and environmental exposure directly from the diseased tissue. As previously suggested from studies with microbial isolates from spatially distinct anatomical lung locations (Chung et al, 2017; Jorth et al, 2015), such variation may be the underlying cause for variation of disease severity within the lung and clinical episodes of exacerbations. Furthermore, the methodology developed herein can be extended to any human organ (notably, organs with tumors, which are known to be associated with their own unique microbiomes (Cavarretta et al, 2017; Cummins and Tangney, 2013; Flemer et al, 2017) and to map and correlate various other types of omics data such as metagenomes and transcriptomes.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Our maps reveal that local environments within the lung vary in terms of pathogen abundance, characteristics of biofilm at the molecular level, pharmaceutical and environmental exposure directly from the diseased tissue. As previously suggested from studies with microbial isolates from spatially distinct anatomical lung locations (Chung et al, 2017; Jorth et al, 2015), such variation may be the underlying cause for variation of disease severity within the lung and clinical episodes of exacerbations. Furthermore, the methodology developed herein can be extended to any human organ (notably, organs with tumors, which are known to be associated with their own unique microbiomes (Cavarretta et al, 2017; Cummins and Tangney, 2013; Flemer et al, 2017) and to map and correlate various other types of omics data such as metagenomes and transcriptomes.…”
Section: Discussionmentioning
confidence: 78%
“…This variation within the organ may result in discrete local microbial niches that contain different subpopulations, which in turn may affect the chemical makeup of these regions (Bumann, 2015). Genome sequencing of microbial isolates from different regions of the lung has accordingly shown variation in subpopulation localization (Chung et al, 2017; Jorth et al, 2015; Willner et al, 2012), and 16S rRNA sequencing of human skin has shown distinct microbial taxonomies across anatomically distinct regions of skin (Bouslimani et al, 2015; Grice et al, 2009; Oh et al, 2014), similar to observations in various other body parts (Human Microbiome Project Consortium, 2012). While metabolomics-based regional variation has been demonstrated by surface mapping of human skin (Bouslimani et al, 2015), the metabolomic volumetric mapping of an entire human organ in 3D, spanning tens of centimeters, has not been performed before.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…For studies investigating serial strains from the same patient, we chose only representative strains, i.e. one sample per patient was chosen from Esposito et al 41 and one strain of the main lineages found by Chung et al 42 . In case of studies providing both NGS data and assembled genomes, we included the NGS data in our analysis.…”
Section: Whole Genome Data Collection and Next Generation Sequencingmentioning
confidence: 99%
“…Data from the literature suggests that, in addition to ESKAPE pathogens, the species Stenotrophomonas maltophilia should be included as a microorganism that causes more and more frequent infections in healthcare settings [1,20,21,22].…”
Section: Risk Factors Of Microbial Infections From Eskape Groupmentioning
confidence: 99%